Trend analysis and projection of gastric cancer burden linked to high sodium intake in China, Japan, Republic of Korea, and Mongolia (1990–2021): A comprehensive assessment based on the 2021 global burden of disease study - Xiaohuang Yang; Shaoxing Chen; Canmei Zhong; Yadong Lai; Fenglin Chen (PLoS ONE, 2025)
Background High sodium intake (HSI) is one of the risk factors for gastric cancer. China, Japan, Republic of Korea, and Mongolia are among the countries with the highest gastric cancer incidence worldwide. This study aimed to assess the burden of gastric cancer linked to HSI in these four countries from 1990 to 2021, and to project future trends. Methods The 2021 Global Burden of Disease (GBD) database was used to analyze trends in HSI-related gastric cancer burden and differences by age and sex in the four countries. Trend changes were evaluated using Joinpoint regression. Decomposition analysis was conducted to assess the relative contributions of demographic aging, population growth, and epidemiological shifts. Future burden was forecast using a Bayesian age–period–cohort (BAPC) model. Results In 2021, the number of gastric cancer deaths in China linked to HSI was 36,958 (95% UI: 0–183,972), with 883,435 DALYs (95% UI: 0–4,461,211). The age-standardized mortality rate (ASMR) was 1.78 (95% UI: 0–8.81) per 100,000, and the age-standardized DALY rate (ASDR) was 41.49 (95% UI: 0–208.59) per 100,000. Across the four countries, the burden of gastric cancer due to HSI was greater in males and elderly groups. Trends in ASMR and ASDR showed consistent declines in all four countries according to Joinpoint analysis. Decomposition analysis demonstrated that epidemiological shifts contributed to easing the burden. The BAPC model projected that the ASMR and ASDR of HSI-related gastric cancer would decrease over the upcoming 15 years in the four countries. Conclusions During 1990–2021, ASMR and ASDR for HSI-related gastric cancer declined in China, Japan, Republic of Korea, and Mongolia, yet differences by sex and age remained. Policymakers need to formulate targeted public health measures in light of these differences.